The Inefficiency of Political Connections Becomes a Boomerang in the Challenge of Sustainable Growth - Riyadi Aprayuda; Fahmi, Fahmi Hidayat (Pusat P2M Politeknik Negeri Batam, 2025)
This study investigates how political connections, board educational background, and carbon emission disclosure affect the Sustainable Growth Rate (SGR) of infrastructure firms listed on the Indonesia Stock Exchange from 2019 to 2023. SGR reflects a firm’s capacity for long-term growth consistent with its financial stability and strategic balance. Using panel data regression with the Random Effects Model (REM), selected based on the Hausman test, this research operationalizes political connections through the presence of politically affiliated commissioners and carbon emissions through disclosure indices. The results indicate that political connections significantly hinder sustainable growth, suggesting that politically connected boards may intensify agency conflicts and weaken governance effectiveness. Meanwhile, board education and carbon emission disclosure show emerging yet statistically weak positive effects, implying that intellectual capacity and environmental accountability are not yet fully embedded in corporate sustainability strategies. Despite the limited sample size, robustness checks confirmed the consistency of the results. Overall, these findings highlight that sustainable growth in Indonesia’s infrastructure sector depends more on governance integrity and managerial competence rather than political privilege. This study contributes to the literature by providing empirical evidence of how agency conflicts arising from political affiliations can undermine long-term corporate sustainability.